Studi Komparasi Strategi True Or False Dengan Index Card Match Terhadap Hasil Belajar Matematika Siswa Kelas IV SD N 5 Ketro Karangrayung Grobogan Tahun Pelajaran 2015/2016 - Exanti, Maya; , Dr. Achmad Fathoni, M.Pd (2016)
ABSTRACT Maya Exanti/A510120226. STUDI KOMPARASI STRATEGI TRUE OR FALSE DENGAN INDEX CARD MATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD N 5 KETRO KARANGRAYUNG GROBOGAN TAHUN PELAJARAN 2015/2016. Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. 14 April, 2016. This study aims to determine: (1) differences in mathematics learning outcomes in the use of True or False strategy with the strategy of Index Card Match on student fourth grade N 5 Ketro Karangrayung Grobogan the academic year 2015/2016, (2) a larger strategy influence between strategy True or False to the Index Card Match strategy against Mathematics student learning outcomes fourth grade N 5 Ketro Karangrayung Grobogan the academic year 2015/2016. This research is quantitative research subjects experiment with grade IV A and IV B SD N 5 Ketro Karangrayung Grobogan. Data collection techniques using tests and documentation. Test instruments such as validity and reliability. Data analysis techniques such as t-test, preceded by a test for normality and homogeneity test. Based on data analysis with significance level of 5% results obtained -tcount  ttable, ie -2.79241  2,01063 with the average value of the results of studying Maths class IV B is greater than the IV B is 91.2 > 81.4. The conclusion of this study are: (1) there are differences in the use of learning outcomes Mathematical True or False strategy with the strategy Index Card Match in class IV SD N 5 Ketro Karangrayung Grobogan the academic year 2015/2016, (2) strategy Index Card Match greater influence True or False strategy rather than on learning outcomes Maths student fourth grade N 5 Ketro Karangrayung Grobogan the academic year 2015/2016. Keywords: Learning Outcomes Mathematics, True or False, Index Card Match.